Collaborative Governance For Developing Tourism Villages In A Literature Review - Dewi, Ni Luh Yulyana; Yanuarta, Naufal Zacky (Pasundan Social Science Development, 2025)
Tourism villages can develop and overcome challenges by adopting a collaborative governance approach, involving all stakeholders in the decision-making and planning process. While collaborative governance may seem beneficial, there are arguments against this approach regarding developing tourist villages. Some critics argue that involving all stakeholders in decision-making can lead to conflicts of interest and slow decision-making. Having a clear hierarchical structure for decision-making, with local authorities and experts at the helm, may be more effective in meeting the immediate needs of rural tourism. This literature review examines the current body of research on the impact of collaborative governance on the development and success of rural tourism. This paper will analyze the benefits and drawbacks of cooperative governance, as well as present case studies that showcase its efficacy in various tourism village settings. The approach involves doing an extensive literature search utilizing databases and pertinent keywords pertaining to collaborative governance and tourist villages. The aforementioned sources offer valuable understanding of the determinants of fair and efficient collaborative governance in the development of rural tourism. The outcomes of this literature review will enhance comprehension of the role of collaborative governance in advancing flourishing rural tourism and offer suggestions for future study and implementation in this domain. The findings indicate that the key factors for achieving suitable and efficient collaborative governance in tourist villages are wide and equitable collaboration, legitimate and competent organizers, and sufficient resources. These decisive characteristics facilitate efficient decision-making, settlement of conflicts, and mobilization of resources for the sustainable growth of village tourism. Ultimately, collaborative governance is crucial in fostering the growth of tourist settlements.